(untitled) - Foreman, Peter; Peter Foreman (Oxford,New York, 2000)
Allegra is an unusual name. It means 'happy' in Italian, but the little girl in this story is sometimes very sad. She is only five years old, but she tells Adrian, her new friend, that she is going to die soon. How does she know? And who is the other Allegra? The girl in a long white nightdress, who has golden hair and big blue eyes. The girl who comes only at night, and whose hands and face are cold, so cold
Keywords: Readers (Adult); English language